Neglected risks in the Chinese insurers’ misconduct caused by digitalization - Jiandi Zhang; Xiaoqing Guo; Rui Xu; Zhengfa Yang (PLoS ONE, 2025)
Digital transformation offers opportunities for innovative growth while also introducing emerging risks of misconduct in the insurance industry. This study examines the impact of digital transformation on insurers’ misconduct, focusing on 72 Chinese insurers from 2010 to 2021. Through text analysis, we quantify insurers’ digital transformation and misconduct. The results indicate that digital transformation tends to increase misconduct, particularly among property insurers and those with joint or foreign ownership. The issuance of digital policy and the adoption of technologies that exceed managerial capacity exacerbate misconduct. Digital transformation drives misconduct through the channels of market expansion and financial pressure. Furthermore, insurers with larger market shares, lower commissions, and operational costs are more prone to misconduct during their digital transformation. Conversely, higher insurance density, market penetration, premium income growth, and lower economic uncertainty help mitigate misconduct.